Steers Afloat: The North Atlantic Meat Trade, Liner Predominance, and Freight Rates, 1870-1913. - Harley, C (Cambridge University Press, 2008)
Meat transformed North Atlantic shipping, leading to dominance of liners and changed the economics of freight rates. Management coordination of meat shipment led to concentration in shipping. Only liner companies could provide specialized ships with the regularity needed and they dominated North Atlantic shipping. The cargo capacity of cattle ships, beyond that used for animals, lowered freight rates on grain below levels that would otherwise have prevailed. The berth rate on wheat from New York to Liverpool was most affected. Consequently, this readily available freight rate can be potentially misleading as an indicator of ocean shipping developments.